Dietary inclusion of arabinoxylo-oligosaccharides in response to broilers challenged with subclinical necrotic enteritis. Issue 4 (4th July 2017) - Keerqin, C.; Morgan, N. K.; Wu, S. B.; Swick, R. A.; Choct, M.
ABSTRACT: 1. This study investigated the prebiotic properties of arabinoxylo-oligosaccharides (AXOS) produced both in situ and in vitro for their activity against the onset of necrotic enteritis in broiler chickens. 2. A 2 × 3 factorial arrangement was applied, including necrotic enteritis challenge (challenged/unchallenged) and three dietary treatments from d 10 to 21. A wheat–soy commercial-type basal-grower diet was fed with 2% of the wheat proportion replaced by the same amount of either arabinoxylan (AX), AXOS produced from hydrolysing AX with 16 000 BXU (birch xylanase unit) xylanase in vitro or AX fed with 16 000 BXU xylanase (AX + E). Necrotic enteritis (NE) challenge was induced by orally infecting birds with a vaccine strain of Eimeria oocysts at d 9 of age followed by oral gavage of a freshly prepared Clostridium perfringens broth at d 14. 3. The challenge depressed growth performance, induced gross lesions and reduced ileal viscosity at d 10–21. Birds fed on the AXOS diet had numerically less severe gross lesions, improved feed conversion at d 0–16 and lower ileal viscosity at d 16 compared to birds fed on AX. Weight gain of the unchallenged birds ranked as follows in terms of the diets: AXOS > AX + E > AX. AX + E produced a lower ileal viscosity compared to the AX treatment but only led to marginal improvements in performance and intestinal lesion scores. 4. Caecal short-chain fatty acid (SCFA) concentration was higher in birds fed on AXOS and AX + E compared to those fed on AX and was higher in the challenged birds compared to the unchallenged birds. Gizzard pH was lower in birds fed on AX + E compared to those fed on AXOS at d 16. Challenged birds had lower ileum pH compared to the unchallenged birds at d 16 and 21. 5. Results of this study suggest that AXOS appeared to be efficacious prebiotics, as highlighted by improvements in feed conversion ratio and increased SCFA production. Future studies are warranted to elucidate the types of AXOS that are most active against NE and the mechanisms by which different levels of AXOS enhance bird performance.